Bridging the Gap: From Photoperception to the Transcription Control of Genes Related to the Production of Phenolic Compounds - Volná, Adriana; Červeň, Jiří; Nezval, Jakub; Pech, Radomír; Špunda, Vladimír (International journal of molecular sciences, 2024)
Phenolic compounds are a group of secondary metabolites responsible for several processes in plants-these compounds are involved in plant-environment interactions (attraction of pollinators, repelling of herbivores, or chemotaxis of microbiota in soil), but also have antioxidative properties and are capable of binding heavy metals or screening ultraviolet radiation. Therefore, the accumulation of these compounds has to be precisely driven, which is ensured on several levels, but the most important aspect seems to be the control of the gene expression. Such transcriptional control requires the presence and activity of transcription factors (TFs) that are driven based on the current requirements of the plant. Two environmental factors mainly affect the accumulation of phenolic compounds-light and temperature. Because it is known that light perception occurs via the specialized sensors (photoreceptors) we decided to combine the biophysical knowledge about light perception in plants with the molecular biology-based knowledge about the transcription control of specific genes to bridge the gap between them. Our review offers insights into the regulation of genes related to phenolic compound production, strengthens understanding of plant responses to environmental cues, and opens avenues for manipulation of the total content and profile of phenolic compounds with potential applications in horticulture and food production.
Keywords: rostliny; transkripční faktory; světlo; Phenols; temperature; Gene Expression Regulation, Plant; Transcription Factors; transcription factors; Light; fenoly; photoreceptors; regulace genové exprese u rostlin; Transcription, Genetic; Plants; radiation; genetická transkripce